PERSEPSI WISATAWAN TERHADAP AKSESIBILITAS DARI PENELOKAN MENUJU OBJEK WISATA TOYA BUNGKAH KECAMATAN KINTAMANI KABUPATEN BANGLI - I Wayan Agus Slamet; I Nyoman Sudiarta; I Wayan Suardana (Jurnal IPTA (Industri Perjalanan Wisata), 2015)
The perception of tourist about accessibility from Penelokan village to Toya Bungkah destination” has objective to known the tourist perceptions of accessibility in Toya Bungkah destination. Kinds data used are primary data and secondary data. The data was gain through observations, depth interviews, questionnaires, literature studies, and documentations. Sampling was gain by purposive sampling to option the data of accessibility. The respondents was choose by using quota sampling. Analyzed the perception of tourist by using attitude scale (Likert scale) to measure the results. The result of the research showed that the tourist perceptions of accessibility to Toya Bungkah were : Condition about access from Penelokan to Toya Bungkah get average score was 3.10 is good enough, Quality of access from Penelokan to Toya Bungkah get average score was 3.20 is good enough, Comfortable of access from Penelokan to Toya Bungkah get average score was 3.14 is good enough, Condition transportasion after arrived from Penelokan to Toya Bungkah get average score was 3,48 is good, View at around access the tourist can see from Penelokan to Toya Bungkah get average score was 4.08 is good, Safety with the path from Penelokan to Toya Bungkah get average score was 3.50 is good, Perception of the tourist about Toya Bungkah get average score was 3.76 is good.